Spike Lee - McGowan, Todd (Book collections on Project MUSE., 2014)
Since the release of Do the Right Thing in 1989, Spike Lee has established himself as a cinematic icon. Lee's mostly independent films garner popular audiences while at the same time engaging in substantial political and social commentary. He is arguably the most accomplished African American filmmaker in cinematic history, and his breakthrough paved the way for the success of many other African Americans in film. In this first single-author scholarly examination of Spike Lee's oeuvre, Todd McGowan shows how Lee's films, from She's Gotta Have It through Red Hook Summer, address crucial social issues such as racism, paranoia, and economic exploitation in a formally inventive manner. McGowan argues that Lee uses excess in his films to intervene in issues of philosophy, politics, and art.